Microfabricated Engineered Particle Systems for Respiratory Drug Delivery and Other Pharmaceutical Applications. (9th February 2012) - Garcia, Andres; Mack, Peter; Williams, Stuart; Fromen, Catherine; Shen, Tammy; Tully, Janet; Pillai, Jonathan; Kuehl, Philip; Napier, Mary; DeSimone, Joseph M.; Maynor, Benjamin W.
Abstract : Particle Replication in Non-Wetting Templates (PRINT ® ) is a platform particle drug delivery technology that coopts the precision and nanoscale spatial resolution inherently afforded by lithographic techniques derived from the microelectronics industry to produce precisely engineered particles. We describe the utility of PRINT technology as a strategy for formulation and delivery of small molecule and biologic therapeutics, highlighting previous studies where particle size, shape, and chemistry have been used to enhance systemic particle distribution properties. In addition, we introduce the application of PRINT technology towards respiratory drug delivery, a particular interest due to the pharmaceutical need for increased control over dry powder characteristics to improve drug delivery and therapeutic indices. To this end, we have produced dry powder particles with micro- and nanoscale geometric features and composed of small molecule and protein therapeutics. Aerosols generated from these particles show attractive properties for efficient pulmonary delivery and differential respiratory deposition characteristics based on particle geometry. This work highlights the advantages of adopting proven microfabrication techniques in achieving unprecedented control over particle geometric design for drug delivery.